Distribution of Hydrocarbon Utilizing Bacterial Population Receiving Hydrocarbon Micro-seepage in Hydrocarbon Exploration Sites of Kukawa North-East Nigeria (Journal of Environmental Bioremediation and Toxicology, 2020)
The search for hydrocarbon has been of great priority for alternative source of energy and economy to many countries. Different types of studies are being conducted to trace specific reservoirs of hydrocarbons. The used of geologic and seismic surveys which are environmental unfriendly and costly requires alternate such as that of microbial survey. The use of culture based method to isolate bacteria with ability to utilize hydrocarbon in survey areas was conducted. Soil sample were collected randomly from all the 13 sample sites from different depths for microbiological analysis. Mineral salt agar supplemented with diesel was used to isolate hydrocarbon utilizing bacteria (HUB). Nutrient agar was used to isolate total heterotrophic bacteria (THB). Soil samples were collected randomly from sample sites at various depths (10, 20 and 30 cm) the bacterial populations at 10 cm depth for HUB was 129×105 to 269×105 CFU/g at Kukawa (KW) and Baga (BG), THB was 122×105 to 266×105 CFU/g at Bundur (BD) and Baga (BG), HUB was 128×105 to 282×105 CFU/g at Kukawa (KW) and Baga (BG), THB was 110×105 to 220×105 CFU/g at Alagarno (AL) and Bawarti (BW) in 20 cm depth. The HUB count at 30 cm depth was 128×105 to 285×105 CFU/g at Kukawa (KW) and Baga (BG), THB counts was 72×105 to 147×105 CFU/g at Alagarno (AL) and Kauwa (KU). Bacillus, Enterobacter, Actinomycetes and Pseudomonas are the dominant bacterial genera in the sample sites. Bacillus subtilis, Bacillus cereus, Bacillus pumilis, Bacillus megaterium, Bacillus licheniformis, Bacillus lentus, Bacillus azotofomans and Bacillus alvei are among the dominant species of Bacillus in the sample sites. The isolation of these bacterial species in high population projects directly a guaranteed discovery of hydrocarbon reservoir and could be a relatively inexpensive and environment friendly method for hydrocarbon prospecting.
Keywords: Hydrocarbon; Bacteria; Prospecting; Kukawa; micro-seepage